2020
DOI: 10.3390/antiox9100940
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of an Antioxidative System for Salinity Tolerance in Oenanthe javanica

Abstract: Abiotic stress, such as drought and salinity, severely affect the growth and yield of many plants. Oenanthe javanica (commonly known as water dropwort) is an important vegetable that is grown in the saline-alkali soils of East Asia, where salinity is the limiting environmental factor. To study the defense mechanism of salt stress responses in water dropwort, we studied two water dropwort cultivars, V11E0022 and V11E0135, based on phenotypic and physiological indexes. We found that V11E0022 were tolerant to sal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
60
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(60 citation statements)
references
References 131 publications
(149 reference statements)
0
60
0
Order By: Relevance
“…In the current study, a minor decrease in MDA concentration was observed at 200 mm NaCl in the leaves of both cultivars. 200 mm NaCl might induces salt stress-related genes in the leaves of water dropwort ( Kumar et al, 2020 ). Sustained decreases in MDA accumulation might be due to the activation of PSII core proteins and Rubisco ( Morales and Munné-Bosch, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In the current study, a minor decrease in MDA concentration was observed at 200 mm NaCl in the leaves of both cultivars. 200 mm NaCl might induces salt stress-related genes in the leaves of water dropwort ( Kumar et al, 2020 ). Sustained decreases in MDA accumulation might be due to the activation of PSII core proteins and Rubisco ( Morales and Munné-Bosch, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Relative water content (RWC) of leaves was measured according to the method described by Sarker and Oba (2018) and Kumar et al (2020) . After determining the fresh weight (FW), leaves were immersed in distilled water in a closed Petri dish for 4 h, and the turgor weight (TW) of each leaf was noted.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…We measured the chlorophyll content of salt-treated S. alopecuroides and found that the recovery upregulation occurred at 24 h and 48 h, thereby indicating that S. alopecuroides reduced the influence of salt stress on photosynthesis. Sugars are photosynthates and respiration substrates [ 39 , 40 ], and they provide a carbon skeleton and energy for plant growth. An increase in the soluble sugar content improves cell osmotic regulation and protoplasm protection [ 34 , 38 ].…”
Section: Discussionmentioning
confidence: 99%